Bentuk Kesalahan Diagnosis Permasalahan Siswa Oleh Guru BK Atau Konselor: Identifikasi, Dampak, Dan Upaya Penanganan Yang Tepat Dalam Layanan BK Di MAN 4 Medan - Ade Chita Putri Harahap; Ade Putri wijaya; Robiyatul Adawiyah; Halimah Musfira; Muslimah Berasa; Zurriyati Putri; Sopia Barira; Aryanti Devi Harahap (Universitas Maritim AMNI Semarang, 2023)
The misdiagnosis of student problems by guidance counselors or BK teachers is a serious concern in counseling services at MAN 4 Medan. This study aims to identify the forms of misdiagnosis of student problems by guidance counselors or BK teachers, the impacts of misdiagnosis, and appropriate handling efforts in BK services at MAN 4 Medan. This study used a qualitative approach with data collection techniques in the form of in-depth interviews, observations, and documentation. The informants in this study were three guidance counselors or BK teachers and ten students from grades X and XI. Data were analyzed using qualitative data analysis techniques. The results showed that the forms of misdiagnosis of student problems by guidance counselors or BK teachers consisted of three types, namely errors in identifying problems, errors in evaluating problems, and errors in determining actions. The impact of misdiagnosis was the incorrect handling of student problems, resulting in problems not being resolved well and potentially worsening the situation for students. Appropriate handling efforts in BK services at MAN 4 Medan include improving the quality of training and supervision for guidance counselors or BK teachers, increasing collaboration between guidance counselors or BK teachers and subject teachers and parents, and increasing the utilization of information and communication technology in counseling services. In conclusion, misdiagnosis of student problems by guidance counselors or BK teachers has a significant impact on students and requires appropriate handling efforts in BK services. Therefore, there needs to be serious attention to the implementation of BK services at MAN 4 Medan to avoid misdiagnosis that can harm students.